The first Muslims history and memory - Afsaruddin, Asma (Oneworld Book, 2009)
The First Muslims reconstructs the first century of Islam to offer a fascinating exploration of the origins and development of the religion. Using a wealth of classical Arabic sources, it chronicles the lives of the Prophet Muhammad, his Companions, and the subsequent two generations of Muslims, together known as the "Pious Forbears"." "Focusing on both the people and their beliefs, Afsaruddin presents a critical examination of the continuing influence of these first Muslims in contemporary times as figureheads for a variety of causes, from liberal Islam to hard-line "fundamentalism". Essential reading for anyone interested in the earliest history of Islam and its impact on Muslims today, this important book will captivate the general reader and student alike.